Apigenin loaded PVA/DMSO hydrogel: cytotoxicity, antimicrobial activity, antioxidant activity and delivery profile - Velásquez López, Paolo Antonio (2024)
This research delves into the analysis of apigenin-loaded PVA/DMSO hydrogel solutions, focusing on their antioxidant activity and delivery profile. A meticulously constructed calibration curve, derived from known apigenin concentrations in PBS solution, serves as the basis for assessing delivery profiles through linear, polynomial, and exponential regression models. While the linear and polynomial models display limitations in accurately representing the data, the visually guided exponential model emerges as a more fitting option. The Apigenin loaded-hydrogel exhibits promising antioxidant activity, synergistically enhancing effects with apigenin. Cytotoxicity assays reveal a negative impact on cell viability without inducing significant toxicity. Antimicrobial assays, however, report no efficacy against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) ECBI-UITEY. The study envisions potential therapeutic applications for the hydrogel in controlled drug delivery, emphasizing the imperative for further validation and optimization in future research endeavors.